Analisis Pengaruh Promosi, Kualitas Informasi Dan Brand Image Terhadap Keputuan Pembelian Online Pada Konsumen Di Akun Instagram Mamoru Store - Roni Angga Saputra; Muhammad Mansur; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of Promotion, Information Quality and Brand Image on purchasing decisions, the sample of this study is the number of Mamoru Store followers. For data collection using a questionnaire, to analyze data using validity test, reliability test, normality test, multiple linear analysis, F statistical test and t statistical test, the coefficient of determination test in the IBM Social Sciences Statistical Package (SPSS) Version 16.0From the results of calculations with SPSS which are promotion variables, information quality and brand image simultaneously and significantly influence purchasing decisions. While partially the promotion variables, information quality and brand image have a positive and significant influence on purchasing decisions. Keywords: Promotion; Information quality; Brand Image; Buying decision